INDEKS PERTUMBUHAN IKAN KAKAP MERAH DAN KERAPU LUMPUR PADA PERIKANAN BUBU DASAR DI PERAIRAN BUNYU - Muhammad Firdaus; Gazali Salim; Jimmy Cahyadi; Encik Weliyadi (Fakultas Perikanan dan Ilmu Kelautan, 2020)
Bunyu Island in the North Kalimantan province has abundant and economically valuable marine aquatic ecosystem resources, where Bunyu Island communities utilize the potential of marine aquatic ecosystems to be used as fishery potential in terms of fishing using bottom fish pots. Fishing catch is economically valuable in the form of red snapper and grouper fish found in the marine ecosystems of Bunyu Island. The research objective was to analyze the growth and size structure of the Red Snapper fish (Lutjanus argentimaculatus) and Grouper fish (Epinephalus malabaricus) originating from the waters of the island of Bunyu. Retrieval of data in the form of growth parameters are the total length and standard length, total weight, gender, gonad maturity level, and gonad weight. The results of the study of most snapper caught the length of 40,49-47,61 cm and a weight of 990,05-1.451,68 grams. While the results of the grouper study most caught were 43,73-50,13 cm in length and weights of 800,94-1.308,70 grams. The nature of growth of Red Snapper fish (Lutjanus argentimaculatus) are negative allometry. The condition index value is skinny of Red Snapper fish (Lutjanus argentimaculatus). Grouper fish (Epinephalus malabaricus) of total length and total weight is positive allometry and on the standart and fork length with total weight is negative allometri.